(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the Uzbek national word games, their types and their specific features are analyzed by the example of advertising text. The manifestation of word games on language levels is explained by linguistic evidence that its types, such as "phonostilistic game", "Phonographic game", "lexical-semantic game", "morphological game", "syntactic game" are the main stylistic figura that forms the advertising text.